Powers That Be? Political Alignment, Government Formation, and Government Stability - Felipe Carozzi; Davide Cipullo; Luca Repetto (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study how partisan alignment across levels of government affects coalition formation and government stability using a regression discontinuity design and a large dataset of Spanish municipal elections. We document a positive effect of alignment on both government formation and stability. Alignment increases the probability that the most-voted party appoints the mayor and decreases the probability that the government is unseated during the term. Aligned parties also obtain sizeable electoral gains in the next elections over unaligned ones. We show that these findings are not the consequence of favoritism in the allocation of transfers towards aligned governments.
Keywords: D72; H20; H77; 330; government stability; government formation; political alignment; inter-governmental relations